Pengaruh Kesehatan Mental dan Lingkungan Kerja Non Fisik Terhadap Kinerja Karyawan pada Karyawan Generasi Z di Kota Bekasi - Wita Safitri; Imelin Sagita S Pardosi; Nurul Hanifa Triyanti (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to examine the relationship between mental health, non-physical work environment, and the performance of generation Z employees in Bekasi City. Generation Z, who were born between 1995 and 2010 or are currently in the age range of 13-28, are known for their characteristics that include high proficiency in using technology, high levels of involvement in social media. However, Generation Z employees have negative characteristics, namely being easily anxious and stressed when things don't go as they wish. Generation Z feels stress at work caused by their perception of a very competitive work environment, long working hours, and tight deadlines in completing their tasks. This study uses a qualitative method through the distribution of questionnaires. The population in this study were 50 generation Z employees in Bekasi City. This study tested the hypothesis and analyzed the data using SmartPLS (Partial Least Square) Computer Software version 3.0. The results of the analysis show that the influence of mental health has a significant influence on employee performance, while the influence of the non-physical work environment has a significant influence on employee performance.